Ewolucja stosunków chińsko-indyjskich w latach pięćdziesiątych XX wieku - Maj, Joanna (Acta Universitatis Lodziensis. Folia Historica, 2008)
Regarding the size of their territories and the number of population, China and India take an important place among Asian countries. Since the appearance of independent India (1947) and the People’s Republic of China (1949) on international arena, the terms of these countries have gone through all possible sorts of stages. The present study investigates the Sino-Indian relations in nineteen fifties, which can be divided into three principal stages. 1950-1954, when India supported the Republic of China on international area, however, without definite political resonance on the part of the Chinese; the period of Sino-Indian cooperation on international forum as well as bilateral contacts on political, economical and cultural grounds in 1954-1957, and the stage from 1958 that has been characterized by anti-Indian attitude of Chinese governmental circles. The complexity of the relations was to a large scale the result of Chinese policy rather than the position of Indian government, regarded as more stable and consistent. It was the Chinese foreign policy that affected the climate of relations between both nations, and dramatic turns in these contacts resulted not only from change of selection of means to achieve Chinese basic political aims but also internal situation in Communist China. However, one should bear in mind that it was India that were more active in the period of creating these relations. Indian authorities believed that it was their responsibility to continue the millennial tradition of peaceful relations with China, although it mainly resulted from the existence of natural Himalayan border, making land military penetration impossible. The friendly relations with China were closely connected with J. Nehru’s conception to grant Asia a proper position in international relations. In these plans, India was about to play a part of the spokesman of Asian nations and the initiator of cooperation, which could have become an example for liberating colonial countries and also an alternative to double-blocked policy. Therefore, mainly because of these reasons, India had been insistently supporting the People’s Republic of China on international arena. Not to complicate Sino-Indian relations, India had given up traditional policy of supporting pro-independence endeavours of Tibet. The real symptom of Sino-Indian international cooperation was the settlement of common conception of creating ‘a peace zone’ in Asia region that was promoted in policy of these countries in years 1954-1957. The above mentioned initiative assumed the avoidance of conflicts among Asian countries with common efforts and diplomatic consultations supported also by countries outside Asian continent. It was in middle fifties when the premises of struggle for leadership in the area of Asia already appeared. The disturbing with regards of international aspect of Sino-Indian rivalry about leadership in Third World was revealed. First of all, Chinese and Indian businesses clashed on plain of international safety in Himalayan region. The safety had been violated by already mentioned different interpretation of borders, as well as policy of sides in neighboring countries of Burma, Nepal, Bhutan and Sikkim. The fact of the existence of the border divergences may not have led to armed conflict between China and India, as in principle controversial regions did not matter economically. In fact, the border dispute became a pretext in strife about hegemony in Asia.